Using phosphor ZnB2O4:Mn2+ for enhancing the illuminating beam and hue standard in white light-emitting diodes - Ha Thanh Tung; Huu Phuc Dang (Universitas Ahmad Dahlan, 2023)
The enhancement in hue uniformity and luminous production of multiple-chip white LED lamps (MCW-LEDs) using dual-layer remote phosphor packaging designs are the emphases of this paper. We blended Mn2+ activated strontium–barium silicate (ZnB2O4:Mn2+) with the phosphor mixture and manage to record significant impacts of this new phosphor mixture on the LED lights’ lighting performance. There is evidence that the growing concentration of yellow-green-emitting ZnB2O4:Mn2+ phosphor encourages the enhancement of hue uniformity and illumination effectiveness in MCW-LEDs with mean correlated hue heats (CCTs) of roughly 8500 K, though the color quality scale is gradually deteriorating. It is possible to successfully achieve such amazing MCW-LED performance if we choose the right concentration and size of ZnB2O4:Mn2+.